견갑골의 방골성 연골지방종: 증례 보고 - 장연; 유지영; 공준석; Yeon Jang; Ji Young Yoo; Joon Seog Kong (Journal of the Korean Society of Radiology, 2024)
Parosteal lipoma is a rare tumor that occurs very close to the bone, and accounts for approximately 0.3% of all lipomas. Chondrolipoma, a lipoma with cartilaginous metaplasia, is also a rare tumor consisting of mature adipose and cartilage tissues. Therefore, a tumor with characteristics of both parosteal lipoma and chondrolipoma simultaneously is extremely rare. Herein, we report the imaging findings of a parosteal chondrolipoma arising in the right periscapular area, confirmed based on surgical resection and histopathologic examination. 방골성 지방종은 뼈에 매우 인접한 위치에 생기는 지방종으로 전체 지방종의 약 0.3%를 차지하는 드문 종양이다. 한편 연골지방종은 지방종에서 연골 화생이 발생한 것으로 성숙한 지방조직과 연골조직으로 이루어져 있으며 매우 드물게 보고되고 있다. 따라서 방골성 지방종과 연골지방종의 특징을 모두 보이는 경우는 더욱 드물다. 저자들은 우측 견갑골 부위에 만져지는 덩이 및 통증을 주소로 내원한 55세 여자 환자가 광범위 절제술 후 조직병리검사에서 방골성 연골지방종으로 진단된 증례를 영상 소견을 중심으로 보고한다.